Violence in elderly in times of the Covid-19 pandemic: an integrative literature review (Research, Society and Development, 2022)
Introduction: This research aims at the panorama of violence against the elderly in the period of the Covid-19 pandemic in Brazil and in the world. Methodology: This is an integrative literature review, carried out in databases: National Library of Medicine (PubMed) and the Library Virtual were the Latin American and Caribbean Literature on Health Sciences (LILACS) and the Nursing Database (BDENF). The following Health Science Descriptors (DeCS-MeSC) were used: Elderly; Violence against the elderly; abuse against the Elderly; Covid-19 pandemic. Results: A total of 92 articles were found. The selection to end or reduce bias was performed by pairs, 13 from the PubMed database and 79 from the VHL (LILACS and BDENF). After methodological rigor through the inclusion and exclusion criteria, 17 articles were selected, of which 02 were repeated and 06 were excluded because they were incomplete and/or did not fully address the theme, totaling 09 articles recruited for this research, 02 of which from PubMed and VHL and 07 from VHL (LILACS and BDENF). Conclusion: The increase in the number of cases of violence still in the current Covid-19 pandemic was strongly witnessed in the elderly population. More studies need to happen to detail this scenario.